PENENTUAN REKOMENDASI MATAKULIAH YANG BERPENGARUH DALAM DUNIA KERJA DENGAN C4.5 - Harvian, Rayvaldi; Mulyawan, Bagus; Sutrisno, Tri (Jurnal Ilmu Komputer dan Sistem Informasi, 2022)
Education is closely related to the world of work, so we need a system that helps provide an overview of the courses needed by the company. It is hoped that the application of course recommendations that have an effect on the world of work will attract many students who can work in accordance with the desired company and are ready to face competition in the world of work. This application is designed to aim to provide recommendations for courses that are influential in the world of work so that students who are running lectures can use this application to make it easier to get information about the courses needed by the desired company so that students have no difficulty in choosing courses that are influential in the world work. In providing course recommendations, a method is needed, namely using the C4.5 Algorithm to make decisions and this application is made using the Javascript programming language and uses the MongoDB database system. In testing the method, accuracy is needed using a confusion matrix with several test schemes and the highest level of accuracy is using 50% data training and 50% data testing with 80% accuracy. Based on the tests carried out, this application can assist students in making decisions to choose the required courses and see the minimum achievements that must be passed to be able to work on the desired job.